2018
DOI: 10.3390/molecules23123139
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of 2N1HIA (2-(3-(2-Fluoro-4-Methoxyphenyl)-6-Oxo-1(6H)-Pyridazinyl)-N-1H-Indol-5-Ylacetamide) on Osteoclast Differentiation via Suppressing Cathepsin K Expression

Abstract: Osteoclasts are large multinucleated cells which are induced by the regulation of the receptor activator of nuclear factor kappa-Β ligand (RANKL), which is important in bone resorption. Excessive osteoclast differentiation can cause pathologic bone loss and destruction. Numerous studies have targeted molecules inhibiting RANKL signaling or bone resorption activity. In this study, 11 compounds from commercial libraries were examined for their effect on RANKL-induced osteoclast differentiation. Of these compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Bone marrow macrophage cells (BMMs) were isolated from femurs and tibias of 8- to 10-week-old C57BL/6J females, as described previously [45]. Briefly, the cells were cultured in alpha minimal essential medium (a-MEM, Thermo Fisher Scientific, Waltham, MA, USA) supplemented with 10% FBS containing 30 ng/mL M-CSF (PeproTech, NJ, USA) for three days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone marrow macrophage cells (BMMs) were isolated from femurs and tibias of 8- to 10-week-old C57BL/6J females, as described previously [45]. Briefly, the cells were cultured in alpha minimal essential medium (a-MEM, Thermo Fisher Scientific, Waltham, MA, USA) supplemented with 10% FBS containing 30 ng/mL M-CSF (PeproTech, NJ, USA) for three days.…”
Section: Methodsmentioning
confidence: 99%
“…Primary mouse osteoblasts were isolated from the calvaria of three-day-old C57BL/6J mice [45]. The cells were cultured in α-MEM with 10% FBS and differentiated into osteoblast by addition of 100 ng/mL BMP-2 (Sino Biological, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, we reported several compounds that target osteoclast inhibition [ 22 , 23 , 24 ]. In the present study, we selected a new chemical with a structure similar to that of previously reported chemicals that exhibit strong inhibitory effects on osteoclast differentiation in vitro, as well as an effect in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…OC expresse tartrate-resistant acid phosphatase (TRAP), calcitonin receptors, 1,2 and cathepsin-K. 3 OC differentiate from monocyte/macrophage precursors in response to two hematopoietic factors, the receptor activator of nuclear factor-κB ligand (RANKL) and macrophage colony-stimulating factor-1 (MCSF1). The main function of OC is to resorb bone.…”
Section: Introductionmentioning
confidence: 99%